COOPERATIVE SOCIETIES AS A CONDUIT FOR ENHANCING AGRICULTURAL EXTENSION CAPABILITIES FOR IMPROVED CROP PRODUCTION (FUDMA JOURNAL OF SCIENCES, 2020)
Of late, the cooperative option has come into focus as a viable medium to effectively mobilize farmers to form groups and pool their resources together, so as to become more effective in agricultural production. It is against that backdrop that this study employed primary data obtained from a sample of 120 crop farmers in Iwo LGA of Osun State to ascertain their participation in cooperatives, assess their perception of cooperatives, identify the factors that significantly influence their decision to participate in cooperatives, and to investigate the challenges confronting cooperatives. The objectives were actualized using descriptive statistics, Likert type scale, binary logit regression and Kendall’s coefficient of concordance, respectively. The results revealed that the level of participation of crop farmers in cooperative societies is low. However, respondents were of the perception that cooperatives provide easy access to loans, improve farmers’ welfare, provides medium for exchange of knowledge, and provides access to information regarding best practices in crop production and marketing. Gender, land size, major occupation, and farming experience were the factors that exert significant influence on crop farmers’ participation in cooperatives in Iwo LGA. Furthermore, inadequate capital emerged as the most severe constraint confronting cooperatives, whereas lack of appropriate medium for dissemination of information was the least pressing constraint. It is recommended that synergistic relationship involving the public sector, private actors and community members should be put in place, so as to create awareness and enlighten crop farmers regarding the potentialities of cooperative societies.
Keywords: Binary Logit Regression, Cooperative Societies, Crop Farmers, Iwo LGA